2016
DOI: 10.1186/s13017-016-0102-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open appendectomy: a retrospective cohort study assessing outcomes and cost-effectiveness

Abstract: BackgroundAppendectomy is the most common surgical procedure performed in emergency surgery. Because of lack of consensus about the most appropriate technique, appendectomy is still being performed by both open (OA) and laparoscopic (LA) methods. In this retrospective analysis, we aimed to compare the laparoscopic approach and the conventional technique in the treatment of acute appendicitis.MethodsRetrospectively collected data from 593 consecutive patients with acute appendicitis were studied. These comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
5
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 47 publications
13
116
5
11
Order By: Relevance
“…The mean age difference was not statistically significant (p>0.05) between two groups. In study of Biondi et al 13 showed the mean age was found 29.66±15.13 years in OA group and 27.75±14.24 years in LA group. The mean age difference was not statistically significant (p>0.05) between two groups.…”
Section: Figure-i: Organisms Isolated From Ssi Wounds Discussionmentioning
confidence: 88%
“…The mean age difference was not statistically significant (p>0.05) between two groups. In study of Biondi et al 13 showed the mean age was found 29.66±15.13 years in OA group and 27.75±14.24 years in LA group. The mean age difference was not statistically significant (p>0.05) between two groups.…”
Section: Figure-i: Organisms Isolated From Ssi Wounds Discussionmentioning
confidence: 88%
“…LA was usually associated a shorter hospital stay and lower incidence of wound infection. [2,3,9]. Mean operation time of LA could be similar or shorter comparing to the OA [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic appendectomy (LA) has been recognized as a standard procedure in the treatment of appendicitis because the procedure was associated with a shorter hospital stay and lower incidence of wound infection [1][2][3][4]. LA rate significantly increased in United State [5].…”
Section: Introductionmentioning
confidence: 99%
“…Наиболее изученным является вопрос сравнитель-ной клинико-экономической эффективности лапароско-пической аппендэктомии по сравнению с открытой мето-дикой как у детей, так и у взрослых [83,84]. Доказано достоверное снижение длительности болевого синдрома в 2-3 раза, а значит, и затрат на обезболивание; сниже-ние количества осложнений на 70-75%, а значит, сокра-щение длительности пребывания пациента на койке, длительности послеоперационной инфузионной и анти-бактериальной терапии.…”
Section: полный переход клиники на лапароскопический метод в лечении unclassified